Optimization of wavelength assignment for QoS multicast in WDM networks. - Xiao-Hua Jia (IEEE Transactions on communications)
This paper discusses quality-of-service (QoS) multicast in wavelength-division multiplexing (WDM) networks. Given a set of QoS multicast requests, we are to find a set of cost suboptimal QoS routing trees and assign wavelengths to them. The objective is to minimize the number of wavelengths in the system. This is a challenging issue. It involves not only optimal QoS multicast routing, but also optimal wavelength assignment. Existing methods consider channel setup in WDM networks in two separate steps: routing and wavelength assignment, which has limited power in minimizing the number of wavelengths. In this paper, we propose a new optimization method, which integrates routing and wavelength assignment in optimization of wavelengths. Two optimization algorithms are also proposed in minimizing the number of wavelengths. One algorithm minimizes the number of wavelengths through reducing the maximal link load in the system; while the other does it by trying to free out the least used wavelengths. Simulation results demonstrate that the proposed algorithms can produce suboptimal QoS routing trees and substantially save the number of wavelengths